Book Review: Translation Quality Assessment: From Principles to Practice - Rocío Caro Quintana (Universitat Jaume I. Department of English Studies, 2020)
With the growth of digital content and the consequences of globalization, more content is published every day and it needs to be translated in order to make it accessible to people all over the world. This process is very simple and straightforward thanks to the implementation of Machine Translation (MT), which is the process of translating texts automatically with computer software in a few seconds. Nevertheless, the quality of texts has to be checked to make them comprehensible, since the quality from MT is still far from perfect. Translation Quality Assessment: From Principles to Practice, edited by Joss Moorkens, Sheila Castilho, Federico Gaspari and Stephen Doherty (2018), deals with the different ways (automatic and manual) these translations can be evaluated. The volume covers how the field has changed throughout the decades (from 1978 until 2018), the different methods it can be applied, and some considerations for future Translation Quality Assessment applications.